Combining Blockchain and Semantic Technologies: A Survey - Arnold Beckmann (2022 IEEE 1st Global Emerging Technology Blockchain Forum: Blockchain & Beyond (iGETblockchain), 2022)
We survey literature that combines blockchain and semantic technologies. Our findings identify main areas where the combination of blockchain with semantic technologies are considered, and answer key research questions, surveying existing challenges addressed, their advantages, technical perspectives, and future recommendations.